The impact of psychological capital and transformational leadership on organizational citizenship behavior - Choong Mun Yuh, Wendy (2019)
The main objective of this study is to examine the impact of the four dimensions of psychological capital and transformational leadership behavior on organizational citizenship behavior (OCB) among employees in one of the local government institutions in central region of Malaysia. The four dimensions of psychological capital are self-efficacy, hope, resilience and optimism. Respondents of this study were 466 middle level management employees in the local government institution selected using purposive sampling. The instruments used in this study were Organizational Citizenship Behavior Questionnaire (OCBQ), Psychological Capital Questionnaire (PCQ) and Multifactor Leadership Questionnaire (MLQ). Data collected were analyzed using Statistical Package for Social Science (SPSS) version 23. Descriptive analysis, reliability analysis, Pearson correlation analysis and multiple regression analysis were conducted to analyze the data. Results from multiple regression analysis indicated that self-efficacy and hope were not significantly related to OCB while resilience reported negative significance with OCB. Optimism and transformational leadership were found to be positively and significantly related to OCB with transformational leadership reporting the highest significance.